Ownership structure and corporate voluntary disclosures in transition economy - Masum, Mofijul Hoq; Abdul Latiff, Ahmed Razman; Osman, Mohammad Noor Hisham (Korea Institute of Science and Technology Information, 2020)
The study aims to investigate the impact of ownership structure on corporate voluntary disclosure in the listed companies of Bangladesh. While many studies on the impact of ownership structure on voluntary disclosure have looked at developed and developing countries, few studies have been carried out in a transition economy. Using a three-step relative voluntary disclosure index, the study applies a multivariate analysis on the cross-sectional data for the year 2018. The findings indicate that the quality of voluntary disclosure in transition economy is still below average but has improved compared to findings from the previous literature. We found a significant inverse relationship between corporate voluntary disclosure and public ownership, while no significant relationships between voluntary disclosure and institutional ownership, director ownership, and foreign ownership have been found. The empirical findings of the study will provide evidence to promote the voluntary disclosure characterized by the ownership structures. The findings have important implications for both local and foreign investors as they make their investment decisions especially related to a transition economy. Besides, the findings will assist, not only the corporate executives in rearranging their reporting paradigm, but also the regulators and governments in similar transition economy in adopting and formulating their corporate policies and strategies.